Identification of Factors Related to Cases of Benign Paroxysmal Positional Vertigo Refractory to Canalicular Repositioning Maneuvers and Evaluation of the Need for Magnetic Resonance Imaging in their Management: Retrospective Analysis of a Series of 176 Cases - Carnevale, Claudio; Til Pérez, Guillermo; Arancibia Tagle, Diego; Tomás Barberán, Manuel; Sarría Echegaray, Pedro (International Archives of Otorhinolaryngology, 2019)
Introduction Benign paroxysmal positional vertigo (BPPV) is the most common form of peripheral vertigo, and, in most cases, it presents a favorable prognosis. The treatment is based on a series of specific canalicular repositioning maneuvers that offer an efficacy close to 100%. Despite this, there are cases that are refractory to treatment, with the persistence of the vertigo symptoms.Objectives The objective of the present paper is to analyze the factors associated with an increased risk of refractory BPPV and the importance of nuclear magnetic resonance in the study of these patients.Methods We retrospectively reviewed the cases of 176 patients diagnosed with BPPV in our center. We divided them into two groups: responders and non-responders to the treatment, and analyzed the possible risk factors associated with a higher risk of refractory vertigo. Fischer exact test was used.Results We found 11 cases refractory to treatment; all of them underwent magnetic resonance imaging (MRI) with gadolinium according to our protocol. Of these, four had an otoneurologic background or pathology, and two other patients presented a multicanal involvement. The difference between the two groups was statistically significant (p < 0.05).Conclusion Otoneurologic background and multicanal involvement were associated with a higher risk of refractory BPPV. When dealing with a BPPV with persistent symptomatology/nystagmus or with early relapse after an initial improvement, other entities that enter into the differential diagnosis must always be considered. We consider it essential to perform an MRI with gadolinium to rule out cases of BPPV that have a central cause.
Keywords: vertigo; positional vertigo; central origin